A comparative study of Mongolian medicine prescriptions in the Chinese Pharmacopoeia and Tibetan medicinal compounds in the Ministerial Standards - Ji Zang; Cai Rang-Zhou Tai; Jie-Jia Nan; Cai Rang-Nanjia (World Scientific Publishing, 2024)
Objective: To analyze the similarity between Mongolian medicine prescriptions included in the 2020 edition of the Pharmacopoeia of the People's Republic of China (hereinafter referred to as the Chinese Pharmacopoeia) and Tibetan medicinal compounds according to the Drug Standards of the Ministry of Public Health of the People's Republic of China: Tibetan Medicine (Volume I) (hereinafter referred to as the Ministerial Standards). Methods: A comparative analysis was conducted between Mongolian medicine prescriptions contained in the Chinese Pharmacopoeia and the corresponding Tibetan medicinal compounds included in the Ministerial Standards using Jaccard similarity coefficients and Hellinger distance algorithms across three dimensions: composition, shared drug dosage ratio, and efficacy. Different weights were applied to calculate the comprehensive similarity between the formulas. Simultaneously, we collated and verified the original source literature, and determined the era of composition for each formula. Results: The overall similarity between the Mongolian medicine prescriptions from the Chinese Pharmacopoeia and the Tibetan medicinal compounds from the Ministerial Standards was over 50%. Notably, the composite similarity for the pairings Sanwei Jili San and Sanwei Jili Tangsan, as well as Wuwei Qingzhuo San and Shiliu Anzhi Jinghua San, exceeded 90%. Additionally, six sets of formulas achieved a similarity of over 75%. Literature research has revealed that all 13 sets of formulas first appeared in Tibetan medical literature and were long-standing practices in Tibetan medicine clinics, significantly predating their initial documentation in Mongolian medical literature. Conclusion: The 13 sets of Mongolian medicine prescriptions originated from Tibetan medicinal compounds. Throughout their evolution, the sets adhered to the principles of similar origins and/or properties and effects, leading to the emergence of both commonly used and alternative items. Nevertheless, the efficacy of the formulas has remained highly consistent. The phenomenon of ingredient substitution in the formulas could be attributed to various factors, such as resource availability and cognitive differences among inheritance schools. This study has important implications for further comparative research on content quantification and pharmacological activity. Such research could uncover new medicinal varieties, fostering the sustainable development of Tibetan and Mongolian medicine.